Faith, Fear, and the Constitution: Religious Freedom and Identity Politics in Indonesia’s Constitutional Jurisprudence - Muhtar Said; Ridwan Arifin; Zaka Firma Aditya (Indonesian Constitutional Studies, 2025)
This study investigates how Indonesia’s Constitutional Court has navigated the dialectic of faith, fear, and the Constitution in its jurisprudence on religious freedom, with particular attention to the implications for pluralism and democratic sustainability. The primary objective is to assess whether the Court has upheld constitutional guarantees of religious liberty or accommodated majoritarian pressures by institutionalizing fear as a constitutional principle. Employing a normative legal research method, the study draws upon a statute approach to analyze constitutional provisions, a case approach to scrutinize landmark decisions such as the 2010 Blasphemy Law ruling, a conceptual approach grounded in theories of constitutional pluralism and militant democracy, and a comparative approach referencing jurisprudence in India, Europe, and North America. The results reveal that while the Court affirms religious freedom in principle, its jurisprudence selectively protects faith, privileging majority interpretations and relegating minority beliefs to conditional entitlements. Fear of unrest and disorder has become a central justification for rights restrictions, reshaping constitutional protections into negotiable privileges rather than universal guarantees. The findings demonstrate that the Constitution itself functions as both a site of principle and pragmatism, oscillating between normative commitments to equality and pragmatic deference to political pressures. Sustainable constitutionalism in Indonesia requires reinterpreting the Constitution as a guarantor of pluralism, reinforcing judicial courage, and embedding international human rights standards into domestic jurisprudence. This research contributes to global debates on religion, identity politics, and constitutional democracy in plural societies.